Inflammation and immune activation are associated with risk of Mycobacterium tuberculosis infection in BCG-vaccinated infants - Satti, I; Wittenberg, RE; Li, S; Harris, SA; Tanner, R; Cizmeci, D; Jacobs, A; Williams, N; Mulenga, H; Fletcher, HA; Scriba, TJ; Tameris, M; et al. (Springer Nature, 2022)
Tuberculosis vaccine development is hindered by the lack of validated immune correlates of protection. Exploring immune correlates of risk of disease and/or infection in prospective samples can inform this field. We investigate whether previously identified immune correlates of risk of TB disease also associate with increased risk of M.tb infection in BCG-vaccinated South African infants, who became infected with M.tb during 2-3 years of follow-up. M.tb infection is defined by conversion to positive reactivity in the QuantiFERON test. We demonstrate that inflammation and immune activation are associated with risk of M.tb infection. Ag85A-specific IgG is elevated in infants that were subsequently infected with M.tb, and this is coupled with upregulated gene expression of immunoglobulin-associated genes and type-I interferon. Plasma levels of IFN-α2, TNF-α, CXCL10 (IP-10) and complement C2 are also higher in infants that were subsequently infected with M.tb.